Numerical and experimental study of effect of paraffin phase change heat storage capsules on the thermal performance of the solar pond. Issue 3 (May 2021) - Wang, Hua; Xiaomeng, Ma; Liugang, Zhang; Zhang, Xinmin; Mei, Yanyang; Zhang, Anchao
In this paper, the effect of adding the composite PCM (Phase Change Material) heat storage capsules to the heat storage layer of the salt gradient solar pond on the thermal performance of the solar pond was studied numerically and experimentally. Based on the program-controlled temperature simulation of the solar pond experimental platform, the effect of adding the composite PCM (48–50°C and 58–60°C melting point paraffin) heat storage capsules on the solar pond temperature and stability was studied, and a numerical simulation model was established to be compared by the experimental results. The results showed that the experimental temperature was consistent with the simulation results; the solar pond with PCM capsules had a smaller temperature change range than the conventional solar pond during the phase change process, but it did not have such effect in the non-phase transition process; in terms of flow, the addition of the PCM phase change units could reduce the flow rate of the heat storage zone, and the PCM with a larger latent heat had a more obvious suppression effect on the flow. Therefore, within a certain temperature range, adding PCM units to the solar pond had a positive effect on maintaining the stable temperature and stability of solar pond.